Holocaust Denial The Politics of Perfidy - Wistrich, Robert S. (De Gruyter, 2012)
Holocaust Denial: The Politics of Perfidy provides a graphic and compelling global panorama of past and present variations on this toxic phenomenon. The volume examines right and left wing French negationism, post-Communist Holocaust deniers in Eastern-Europe, the spread of denial to Australia, Canada, South-Africa and even to Japan. Leading scholarly experts also explore the close connection between Holocaust denial, global conspiracy theories, antisemitism and radical anti-Zionism, especially in Iran and the Arab world.